Ответы и объяснения

2014-02-25T11:03:21+04:00
1.(x-3)(x-2)-30-(x^2-9)= x^2-2x+6-30-x^2+9=  -5x-15 = -5(x+3)=     -5        
        (x-3)(x+3)          (x-3)(x+3)              (x-3)(x+3)    (x-3)(x+3)    x-3
 
2.(x-1)(x-2)+5(x+1)-6    = x^2-2x-x+2+5x+5-6= x^2+2x+1= (x+1)^2         x+1   
     (x-1)(x+1)                        (x-1)(x+1)           (x-1)(x+1)     (x-1)(x+1)        x-1
 
 3.(x-1)(x-9)+(x+1)(x+3)-8 =x^2-9x-x+9+x^2+3x+x+3-8= 2x^2-6x+4= (x-2)(x-1)=    x-2
         (x-1)(x+1)                            (x-1)(x+1)                  (x-1)( x+1)   (x-1)(x+1)    x+1
 4.(x-5)(x+1)+9-(x-2)^2=x^2+x-5x-5+9-x^2+4x-4= 0
      (x-2)(x-5)                        (x-2)(x-5)